(untitled) (aSSIST Business Review, 2026)
This study examines the structural limitations of the SWIFT financial messaging system and explores how Ripple’s XRP Ledger presents a strategic alternative for global financial innovation. Unlike SWIFT, which separates messaging and settlement layers, the XRP Ledger integrates them into a single network using the Ripple Protocol Consensus Algorithm (RPCA). Through its On-Demand Liquidity (ODL) mechanism, Ripple enables real-time cross-border transactions without the need for pre-funded accounts. The study applies the SER-M (Subject-Environment-Resource-Mechanism) and Weight-Sequence models to analyze Ripple’s strategic architecture and execution. Key findings highlight XRP’s technology-driven structural innovation, dynamic regulatory alignment, and strategic adaptability through network trust and decentralized governance. The results suggest that XRP offers a scalable and institutionally integrable infrastructure model, serving as a potential blueprint for the next generation of decentralized financial systems.